Frequency of Anemia in Chronic Obstructive Pulmonary Disease (COPD) - Ali Awais Malik, Sohail Anwar, Huma Batool, Asifa Karamat, Ghaniya Ali, Faezah Siddiqui (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Multiple western studies have focused on anemia in COPD and observed that anemia is more prevalent in COPD patients than Polycythemia. Anemia significantly increases the morbidity and deteriorates the functional status of COPD patients. Objectives: The objective of current study was to determine the frequency of anemia in Chronic Obstructive Pulmonary Disease (COPD) patients present in a tertiary care hospital. Study Design: Retrospective Material and Methods: Two hundred COPD patients fulfilling the inclusion criteria were selected for the study. Hemoglobin (Hb) level test was done on all patients. Hb level was calculated by Automated Blood Cell Analyzer and anemia was labeled at Hb<13g/dL Results: The mean of patients’ age was 56.65+ 7.95 years. 181 (90.5%) patients were male and 19 (9.5%) patients were female. The mean Hemoglobin level (Hb) of the patients was 13.46 + 1.45 g/dL. 48 patients (24%) were anemic and 152 patients (76%) were non anemic. Conclusion: The conclusion of the study is there is frequent occurrence of anemia in patients with chronic obstructive pulmonary disease (COPD), as in current study the frequency of anemia was found in 24.0% patients.